2010
DOI: 10.1371/journal.pone.0015693
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Reveals Loci Encoding Anti-Macrophage Factors in the Human Pathogen Burkholderia pseudomallei K96243

Abstract: Burkholderia pseudomallei is an important human pathogen whose infection biology is still poorly understood. The bacterium is endemic to tropical regions, including South East Asia and Northern Australia, where it causes melioidosis, a serious disease associated with both high mortality and antibiotic resistance. B. pseudomallei is a Gram-negative facultative intracellular pathogen that is able to replicate in macrophages. However despite the critical nature of its interaction with macrophages, few anti-macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…3B and 6) as well as transcriptomic analyses by others (16,38), SGSs are the only anopheline or culicine saliva proteins whose mass approximates the value predicted for this ϳ387-kDa protein. In support of our hypothesis that Sgs4 and Sgs5 are immunomodulatory, it has recently been shown that bacterial RHS/YD-repeat proteins (distant relatives of SGS) play a role during the deactivation of human macrophages by the bacterial pathogen Burkholderia pseudomallei (39). If SGSs are indeed immunomodulators, they should be considered when developing transmission-blocking vaccines.…”
Section: Discussionsupporting
confidence: 66%
“…3B and 6) as well as transcriptomic analyses by others (16,38), SGSs are the only anopheline or culicine saliva proteins whose mass approximates the value predicted for this ϳ387-kDa protein. In support of our hypothesis that Sgs4 and Sgs5 are immunomodulatory, it has recently been shown that bacterial RHS/YD-repeat proteins (distant relatives of SGS) play a role during the deactivation of human macrophages by the bacterial pathogen Burkholderia pseudomallei (39). If SGSs are indeed immunomodulators, they should be considered when developing transmission-blocking vaccines.…”
Section: Discussionsupporting
confidence: 66%
“…The expression of B. pseudomallei katG and ahpC is regulated through a global H 2 O 2 sensor and the OxyR transcriptional regulator [2123]. The increased expression of katG and ahpC after exposure to oxidative stress is consistent with the findings from previous studies [22, 23].…”
Section: Resultssupporting
confidence: 87%
“…A marked increase in actin stress fiber formation, very similar in effect to BopE, was observed when BPSL1057F1 was expressed in HeLa cells [31]. A mutant of the hypothetical protein BPSL1528 had severely reduced actin tail formation in HeLa cells while expression of the hemagglutanin FhaB (BPSS1727) in J774.2 macrophages yielded actin projections stretching towards adjacent cells [65,87]. The BPSL1528 mutant also displayed reduced swimming motility and intracellular growth in phagocytic and non-phagocytic cells, suggesting BPSL1528 may act pleiotropically in a regulatory manner [65].…”
Section: Intracellular Motilitymentioning
confidence: 99%
“…It is possible that RpoS may play a role in regulating the transcription of genes whose products are involved in promoting macrophage fusion [84,92]. Ecotopic expression of BPSL0590 and BPSL0591, putative homologs of Photorhabdus luminescens insecticidal toxins, in J774.2 macrophages induced MNGC formation and nuclear apoptosis [87]. BPSS0945, a putative exported peptidase, localized to the nucleus when expressed in HeLa cells and resulted in increased MNGC formation.…”
Section: Mngc Formationmentioning
confidence: 99%